Disassemblability evaluation method (DEM) for green product - Yusof, Yusri (2003)
Disassembly is a fundamental process needed for component reuse and material recycling in all assembled products. Disassembly activities take place in various recovery operations including remanufacturing, recycling, and disposal. Disassembly is often a labor intensive and costly process. Techniques such as design for disassembly (DFD) have been reported in an attempt to lower the high cost of disassembly. Disassembly planning is concerned with finding the optimal sequence of disassembly for a given design. On the other hand, DFD examines the given design to evaluate its "fitness" for disassembly, and where appropriate, to provide high level suggestions to redesign the components so that they are easy to be disassembled. Introduced by Hitachi, Disassemblability Evaluation Method (DEM) analysis is performed when the design details are known (the parts number, types, optimal disassembly sequences, shapes of components and their disassembly relationships). DEM is used to guide the designer in the search for a best initial design to reduce the time and cost. As a result, the researcher investigates detail of the DEM approach from determined the disassembly sequences and determined the score for each part of the original design and give some suggestions to improve the design, finally redesign the product. In this paper, the researcher proposes the case study of the green product, electrical appliance home product to evaluate and to compare the original design and the new design with several parameters. Two main parameters to indicate this evaluation are the E index, (Disassemblability Evaluation Score) and the K index (Disassembly operation cost ratio). Comparison results of the case study had shown the percentages of improvement and reduction of several parameters for the original and new design.